A Review on Ground Water Management (International Journal of Food and Nutritional Sciences, 2023)
Water is the most widely consumed commodity on the planet. Water on Earth comes in avariety of forms. India has 17% of the world's population but just 4% of the world's waterresources, 80% of which are utilized for agriculture. Water consumption in India's cities isabout 40%, causing ground water tables to plummet below 2 to 3 meters per year.